Nudge for (the Public) Good: How Defaults can affect Cooperation - Toke R. Fosgaard; Marco Piovesan (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2015)
In this paper we test the effect of non-binding defaults on the level of contribution to a public good. We manipulate the default numbers appearing on the decision screen to nudge subjects toward a free-rider strategy or a perfect conditional cooperator strategy. Our results show that the vast majority of our subjects did not adopt the default numbers, but their stated strategy was affected by the default. Moreover, we find that our manipulation spilled over to a subsequent repeated public goods game where there default was not manipulated. Here we found that subjects who previously saw the free rider default were significantly less cooperative than those who saw the perfect conditional cooperator default.
Keywords: C90; 330; Cooperation; Nudging